Development of Academic Community Recommendation System Using Content-Based Filtering at UIN Malang Informatics Engineering Study Program - Abdurrozzaaq Ashshiddiqi Zuhri; Ririen Kusumawati; Muhammad Ainul Yaqin; Aldian Faizzul Anwar; Achmad Fahreza Alif Pahlevi (LPPM STIKI MALANG, 2025)
The mismatch between the number and quality of Information and Communication Technology (ICT) talents and industry needs in Indonesia creates significant challenges, especially for Informatics Engineering students who often experience difficulties in determining the appropriate professional field. This research aims to develop a content-based filtering-based academic community recommendation system to help students choose communities that are relevant to their interests, skills and experience. The system uses TF-IDF and cosine similarity methods to match student profiles with community descriptions. Data was collected from 48 students and 10 academic communities in the Informatics Engineering Study Program of UIN Malang, and processed through preprocessing stages before modeling. Evaluation results using the System Usability Scale (SUS) resulted in a score of 76, which is categorized in the â€œgoodâ€ level, However, users indicated the need for improved guidance in navigating the system. This system is expected to be an innovative solution to increase student participation in appropriate academic communities, as well as support the development of their potential and readiness for the world of work